A Case of Multiple Myeloma Misdiagnosed as Seronegative Rheumatoid Arthritis and Review of Relevant Literature. (11th October 2018) - Schoninger, Scott; Homsi, Yamen; Kreps, Alexandra; Milojkvovic, Natasa
Abstract : Multiple myeloma (MM) is a malignant plasma cell proliferation producing large numbers of monoclonal immunoglobulins. Typical MM symptoms include anemia, renal failure, hypercalcemia, and bone pain. Atypical symptoms have rarely been reported in the literature. We report a case of a 58-year-old male who presented with symmetrical inflammatory polyarthritis and was misdiagnosed with seronegative rheumatoid arthritis (RA). After failing many RA treatments and with further workup, the diagnosis of MM was made. This rare manifestation of MM carries a diagnostic challenge and causes a significant delay in treating such patients. Here, we report this unusual initial presentation with review of several cases in the English literature describing similar presentations.